The regional competitiveness: perspective on national resilience - Fachrul Razi; Arthur Josias Simon; Abdul Rivai Ras; Iskandar Abdul Samad (International Journal of Latin Notary, 2022)
A law of regional competitiveness has become important for a country. This issue is one of the eight important elements in national defense. This qualitative research applies focus group discussion and employ 21 participants to gather data. The result shows that the law that regulates the competitiveness is important to increase the life quality of the people.